Politikai küzdelmek a századfordulón a budapesti egyetemi körben (1888–1899) - Varga, Júlia (Gerundium, 2019)
Political Struggles at the Turn of the Century in the University Circle of Budapest 1888–1898. The study presents details about the activities of the, so far quite unknown, University Circle of Budapest in the last decade of the 19th century. Its source is the Egyetemi Lapok university periodical, voicing the political views of the youth. In the writings thereof, the author tries to find sings of how the university students became divided, which manifested itself in the anti-Semitic cross movement in the first year of the new century, in 1901. What led to the principally liberal Hungarian bourgeoisie and gentry youth interested in politics separating itself, or even turning against, their Jewish counterparts, formulating their own interests against them? The Budapest University was one of the prominent locations of the assimilation process of the Jews concentrated in the capital, and the roots of the dividedness of the Hungarian intellectuals may be found in the events, and intellectual reactions, that took place at that time.